Sites of Situated Hope: Amazonian Rhythms, Unruly Caribbean Plants, and Post-Anthropocentric Gazes in Contemporary Latin American Cinema. Issue 4 (2nd October 2022) - Castro, Azucena; Selgas, Gianfranco
Abstract : This article examines the ways in which the cinematic practices of the audiovisual productions Farmacopea (2013) by Beatriz Santiago Muñoz (Puerto Rico) and Río Verde (2017) by Diego and Álvaro Sarmiento (Peru) address human-nature assemblages by articulating a post-anthropocentric gaze. Addressing these two movies as neoregional films, this essay discusses how these contemporary audiovisual productions explore the disastrous environmental histories of the tropical plantation in the Caribbean and the extractive exploitation of the Peruvian-Amazon jungle, exhibiting cinematic techniques that disrupt the socially committed tradition of Latin American cinema of the 1960s centred on human communities. Deploying experimental and poetic cinematic techniques, it is argued that these movies feature small matter by foregrounding local poisonous vegetation and corporal takes of humans and animals that register landscapes in disappearance in the face of modern extractive practices. Departing from Santiago Muñoz's and the Sarmiento brothers' filmic productions, we discuss how the embedding of Amazonian rhythms and unruly Caribbean plants in their filmic narratives produces sites of situated hope that both reconceptualise Latin American cinema and contest the necro-political violence of the modern extractive machinery.